Photodetectors: A Plasmonic Platform with Disordered Array of Metal Nanoparticles for Three‐Order Enhanced Upconversion Luminescence and Highly Sensitive Near‐Infrared Photodetector (Adv. Mater. 36/2016). Issue 36 (September 2016) - Kwon, Seok Joon; Lee, Gi Yong; Jung, Kinam; Jang, Ho Seong; Park, Joon‐Suh; Ju, Honglyoul; Han, Il Ki; Ko, Hyungduk
Abstract : On page 7899, S. J. Kwon, H. Ko, and co‐workers report a promising plasmonic platform, prepared by a randomized array of silver nanoparticles, which greatly boosts near‐IR‐to‐visible (green and red) luminescence from underlying upconversion nanoparticles (pale green particles) and substantially enhances near‐IR photosensitivity. The silver particles in the disordered array effectively work as both plasmonic hot spots and nanoantennas, which notably increases quantum yield and emissivity of the luminescence.